Molecular identification of freshwater snails (Mollusca Gastropoda) from selected rivers in Zamboanga Peninsula, the Philippines - Siglos, Llara M. (Philippine Journal of Science, 2025)
The Zamboanga Peninsula Region has numerous freshwater ecosystems that serve as homes to various snails. However, only a few studies have been conducted on the species richness of freshwater snails in the region. This study aimed to identify freshwater snail species from selected rivers in Zamboanga City and Isabela City of Zamboanga Peninsula using molecular techniques. The foot tissues of the 50 snail samples were used for DNA extraction. The partial MT-CO1 gene was amplified, resulting in 600–700 bp sequences. The amplicons were sent for Sanger DNA Sequencing. Thirty-five (35) of the 50 samples were identified and grouped according to species level. As a result, 11 species were identified – namely Filopaludina luzonica, Indoplanorbis exustus, Melanoides tuberculata, Mieniplotia scabra, Neritina iris, Neritina stumpffi, Physella acuta, Pomacea canaliculata, Radix rubiginosa, Stenomelania torulosa, and Tarebia granifera. The result of the phylogenetic analysis confirmed the identities of these species. However, the partial MT-CO1 gene sequences of the remaining 15 samples were not available in the genetic sequence database of GenBank, NCBI. The unavailability of similar sequences in the database suggests that these freshwater snails might be of different species or might be novel species. The results of this study provide the first record of the molecular identification of freshwater snails in the two cities of the Zamboanga Peninsula. Additional data on the accurate identification of species could help researchers better assess the roles of species in the ecosystem dynamics. Similar studies could also facilitate the discovery of novel species.